PENURUNAN KANDUNGAN GIZI MIKRO KERANG HIJAU (Perna viridis) AKIBAT METODE PEMASAKAN YANG BERBEDA - SRI PURWANINGSIH; ELLA SALAMAH; MERLINDA KEMALA DEWI (Akuatik: Jurnal Sumberdaya Perairan, 2011)
Mineral requirements in humans can be obtained by eating food derived from vegetable or animal. One of the foodstuffs from animal that can contribute for mineral availability in green mussels. The purposes of this study were to determine the types and amounts of macro and micro minerals in green mussel, determine the solubility of Ca, Fe, Zn, and Se in green mussels with three cooking methods (boiling, frying and roasting) and recommend to the public the best way of cooking to obtain mineral nutrient content. In preliminary study conducted proximate analysis includes the moisture content, ash, fat, protein and carbohydrates, and total macro and micro minerals. In further research, green mussel samples that had cooked (boiling, toasting, and baking), were analyzed the solubility of minerals. The highest macro mineral content of the green mussel was sodium content,while the micro minerals of green mussel was selenium. Cooking that gave mineral reduction of at least up to the biggest decline in a row which is the method of cooking by boiling, roasting and frying. Frying reduced mineral content up to 80% while boiling and roasting up to 59% and 69%